Inactivator of the Third Component of Complement as an Inhibitor in the Properdin Pathway - Alper, Chester A. (1972)
Evidence has been obtained that a single protein, known to modulate classical complement activation, also acts as an inhibitor in the properdin or alternate complement pathway. A highly purified inactivator of the third component of complement (C3) from human serum inhibited the proteolysis of Factor B in the properdin system (glycine-rich β-glycoprotein) by glycine-rich β-glycoproteinase. The inhibition was by the enzymatic destruction of glycine-rich β-glycoproteinase activity. The major fragment of C3, C3b, which is the only known substrate of the C3 inactivator, blocked the destruction of glycine-rich β-glycoproteinase by the C3 inactivator. Thus, in its inhibition of the porperdin pathway, the C3 inactivator destroys both the active form of glycine-rich β-glycoproteinase and a protein involved in the conversion of the zymogen form of this enzyme (proglycine-rich β-glycoproteinase) to its active form. The increased susceptibility to infections in a patient homozygous for deficiency of the C3 inactivator demonstrates the biologic significance of this protein.